Revising the Land Law to Enable Sustainable Development in Vietnam : Summary of Priority Policy Recommendations Drawn form World Bank Studies - World Bank (World Bank, Hanoi, 2017)
Vietnam's rapid and sustained economic growth and poverty reduction in the last two decades benefitted from the policy and legal reforms embodied in the Land Laws of 1987, 1993 and 2003 and subsequent related legal acts. This note outlines reforms related to four main themes. The first relates to the needed reform for agriculture land use to create opportunity to enhance effectiveness of land use as well as to secure farmers' rights in land use. Prolonging the duration of agricultural land tenure would give land users greater incentives to invest and care for the land. Raising the land holding ceiling and allowing greater land accumulation would facilitate greater economies of scale, and extending the rights of agricultural land users to alter the land use purpose will further improve efficiency. This scope for more flexible land use will become increasingly important in the context of climate change, with farmers needing to make a range of adjustments based upon expected weather patterns and the associated risks. The second set of priority reforms is to create transparent and equitable land acquisition and compensation by the State. Limiting the use of compulsory land acquisition only to cases for the public's benefit would similarly give land users more fairness and more confidence in their rights related to land. By relying predominantly on voluntary land conversions, there would also be a stronger sense of equity in those cases when land users actually do lose their land. Changing the focus of land compensation pricing (in cases of compulsory land acquisition), and introducing innovations such as benefit sharing, land pooling and land readjustment are also essential for generating a sense of fairness. Creating an efficient grievance redress mechanism at the investment project level would reduce complaints, speed up project implementation and facilitate social stability. A third set of priority reforms is that the land law should offer the opportunity to reaffirm and strengthen the land use rights of vulnerable groups, such as women, the poor and ethnic minority communities. Land management oversight can be made more efficient by amending the land management decentralization and building monitoring and evaluation systems. Expanding the coverage of Land Use Rights Certificates (LURCs) and ensuring the rights and benefits of the land users would further help improve efficiency and fairness. Finally, the fourth set of priority reforms is aimed at making the governance system more effective and accountable. Developing a more flexible and effective land planning management system, and improving transparency of land and anti-corruption in land management are all needed to take Vietnam's land governance system closer to that worthy of a middle income country.